Data from: Free Amino Acids and Sugars in Fifteen Sweetpotato Genotypes: Effects of Curing and Storage on Acrylamide Formation in Fried Chips - MATTHEW ALLAN (18945580) (2025)
The objective of the study was to measure changes in sugars and free amino acids in 15 sweetpotato genotypes before curing, after curing, and over 10 months of storage to investigate the effects on acrylamide formation. The data are of the raw sweetpotatoes (sugar and free amino acids) and chip attributes (oil, acrylamide, color). Materials and Processing: Sweetpotatoes grown in duplicate blocks using conventional practices at the NCDA Research Station in Clinton, NC, USA. Harvested roots were cured (30°C and 85-90% RH) for 7 days, stored at 13-16°C and 80-90% RH for 2, 4, 6, 8, and 10 months. At each timepoint, 7 to 12 sweetpotatoes from each genotype were washed, peeled, and sliced 1.5 mm thick then fried at 157 °C in canola oil for 3 minutes. Raw slices and fried chips were stored at -20 °C until analysis. Raw slices were freeze dried then ground into a powder. Dry matter: Dry matter was determined by drying at 105 °C for 24 h. Chip fat and moisture contents: Chip moisture and fat contents were measured with a Maran NMR analyzer (Resonance Instruments Ltd., Witney, UK). Chip color: Hunter L*, a*, and b* values of crushed chip samples were measured using a DP‐900 Colorimeter (Hunter Associates Lab, Reston, VA, USA) Sugar Contents: One gram of powder was extracted with 20 mL of boiling ethanol, vortexed, incubated held for 15 min, centrifuged, decanted into 50 mL volumetric flask, then repeated. Glucose, fructose, sucrose, and maltose were separated isocratically using 150 mM NaOH at 1 mL/min on a Dionex CarboPac PA-1 (4 x 250 mm) with guard column (4 x 50 mm) and detected with an Antec Scientific (Alphen a/d Rijn, NL) Decade II electrochemical detector. Fried chip sugars were measured in the same matter but after chips were defatted with hexane. Free Amino Acid Analysis: One gram of powder was extracted with 5 mL of 0.1 M HCl, vortexed, incubated at 4 °C for overnight, then centrifuged. The supernatant was used for total free amino group analysis and individual amino acid quantification. For individual quantification, 250 µL of extract was mixed with 250 µL of internal standards in acetonitrile, vortexed, centrifuged, then filtered in a 0.5 mL, 0.22 µm Ultrafree-MC-GV centrifugal filter tube. Amino acids in filtrate were measured using a Shimadzu Nexera-2 UHPLC system with LCMS-8030 plus using electrospray ionization. They were separated using an Atlantis Silica HILIC column (4.6 mm × 100 mm, 3 μm particle size) (Waters Corporation, Midford, MA, USA) at 35 °C and 0.6 mL/min mobile phase A (85% acetonitrile with 0.15% formic acid and 10 mM ammonium formate) and mobile phase B (water with 0.15% formic acid and 10 mM ammonium formate) using the following gradient profile: 0 to 9.6% B from 0 to 3 min; 9.6 to 27% B from 3 to 7 min; 27% B from 7 to 8 min; 27 to 37% B from 9 to 10.5 min; then re-equilibrated with 0% B from 10.5 to 19 min. Glycine was separated isocratically with 0.5% acetonitrile,0.1% acetic acid in water at 0.5 mL/min and 35°C using an Atlantic dc18 column (4.6mm × 100 mm, 3 μm particle size) (Waters Corporation, Midford, MA, USA). Total free amino groups Free amino groups were measured by the o-phthalaldehyde (OPA) method (Church et al., 1983) with and external standard curve of L-leucine dissolved in 0.1 M sodium tetraborate buffer at a pH of 9.0. Acrylamide measurements: One gram of ground chip material was spiked with 0.2 mL of d3-labelled-acrylamide internal working standard (10 μg/ml in 10 mM formic acid) then extracted with 19 mL of 10 mM formic acid by vortexing for 3 min. Carrez I and Carrez II reagents (0.5 mL of each) were added, then centrifuged at 0°C. 1.5 mL of the clarified aqueous supernatant was loaded onto a preconditioned Oasis HLB SPE cartridge followed by a preconditioned BondElut Accucat SPE cartridge. Acrylamide was measured using the same LC-MS/MS system separated isocratically using 10 mM formic acid at a flow rate of 0.3 mL/min at 25 °C on an Atlantis T3 column (150 mm x 4.6 mm, 3 μm). Abbreviations and terms Block: Growing block; Dup: Replicate from the same block; Acn: Acrylamide, GABA: gamma-aminobutyric acid; RS: Reducing sugars; CbRt: cubic root transform; fw: fresh weight; dw: dry weight